Clinical and genetic drivers of oligo-metastatic disease in colon cancer - Alessandro Ottaiano; Mariachiara Santorsola; Roberto Sirica; Annabella Di Mauro; Antonella Di Carlo; Monica Ianniello; Francesco Sabbatino; Rosa Castiello; Francesca Del Peschio; Marco Cascella; Francesco Perri; Maurizio Capuozzo; et al. (Neoplasia: An International Journal for Oncology Research)
Background: Oligo-metastatic disease (OMD) in colon cancer patients exhibits distinct clinical behavior compared to poly-metastatic disease (PMD), with a more responsive and indolent course. This study aims to identify clinical and biological factors uniquely associated with oligo-metastatic behavior. Methods: Metastatic colon cancer patients from an academic center underwent genetic characterization. OMD was defined as ≤3 lesions per organ, each with a total diameter <70 mm and none exceeding 25 mm. Tumor DNA sequencing by NGS utilized the TruSight Oncology 500 kit. Overall survival (OS) was determined from metastasis diagnosis until death using Kaplan–Meier analysis. Multivariate Cox regression examined prognostic links between clinicopathological and genetic factors. Associations with metastatic patterns were evaluated using Chi-square. Results: The analysis involved 104 patients (44 with OMD, 60 with PMD). OMD was more prevalent in males (P = 0.0299) and with single organ involvement (P = 0.0226). Multivariate analysis adjusted for age (>70 vs. <70 years), gender (male vs. female), tumor side (right vs. left), metastatic involvement (more than one site vs. one site), response to first-line therapy (disease control vs. no disease control), and RAS/BRAF variants (wild-type vs. mutated) identified OMD vs. PMD as the strongest independent predictor of survival (HR: 0.14; 95 % CI: 0.06-0.33; P<0.0001). OMD patients exhibited distinct molecular characteristics, including lower frequencies of BRAF p.V600E (P=0.0315) and KRAS mutations (P=0.0456), as well as a higher frequency of high tumor mutational burden (P=0.0127). Additionally, by integrating data from public datasets and our case study, we hypothesize that some gene alterations (i.e.: BRAF, SMAD4, RAF1, and mTOR) may prevent OMD occurrence. Conclusion: OMD, characterized by male predominance, single-site involvement, and distinct molecular features in colon cancer, suggests the need for tailored management strategies.